Biochemical values in the goats’ blood serum related to their physiological states and race in the Brazilian semi-arid Northeast. II. Calcium, phosphorus and magnesium - Unanian, Maria Marina; Silva, Antonio Emidio Dias Feliciano (Pesquisa Agropecuaria Brasileira, 2014)
This study of macro-elements (calcium, phosphorus and magnesium) was undertaken to determine their normal levels in blood-serum of goats maintained in semi-arid Northeast of Brazil. A group of 153 does of mixed Anglo-Nubian, Canindé-Repartida, Marota, Moxotó and SRD breads was used and blood was collected during different physiological states: before pregnancy, during first-third and last-third of pregnancy, and during lactation. The results demonstrated a highly significant difference between breeds and between physiological states (P < 0.0005) regarding calcium levels. The level of phosphorus varied (P < 0.005) between breeds but not between physiological states, and the level of magnesium was not influenced by either of these factors.